Advances in the Application of Simulation Methods for NaCl Diffusion during Salting of Aquatic Products - YANG Kun, WU Runlin, LI Qiqi, LI Kaiqi, XIONG Shanbai, LIU Ru (Shipin Kexue)
NaCl is an essential component of salting ingredients, and NaCl diffusion in aquatic animal muscles significantly influences the microbiology, texture and flavor of aquatic products. Consequently, in order to improve the salting efficiency and product quality, researchers have made extensive efforts on how to control and predict the diffusion of NaCl during the salting process. This paper introduces the current simulation methods of NaCl diffusion from three perspectives: theoretical model, predictive model and finite element analysis. It provides a comprehensive overview of the current status of the application of the three simulation methods as well as their advantages and disadvantages in the salting process of aquatic products. This review aims to provide theoretical and technical references for the innovative development and intelligent production of salted aquatic products.